Area 46 in CAPES: origin, changes and consolidation as “teaching area” in the academic-scientific field - Agostini, Gabriela [UNESP]; Massi, Luciana [UNESP] (Investigacoes em Ensino de Ciencias (IENCI), 2023)
The aim of this article is to investigate how area 46, as an institutionalized space in CAPES, is positioned in relation to the academic-scientific field, disputing spaces of power. This is documentary research, with primary and secondary source texts. Based on Pierre Bourdieu's theory of fields, a socio-analysis of the area was carried out. We seek in each text to analyze the historical facts and the relationships between agents and institutions in the disputes over the area and in the constitution of this space. The analysis covers three important moments that organize the text: i) the context of the origin of area 46 at CAPES; ii) the struggle around the critical moment of change of the area, from Science and Mathematics Teaching to Teaching; iii) its expansion, consolidation, and search for autonomy in the field. The results show that its emergence resulted from several factors and agents interested and positioned for this purpose. From this complex story we highlight the role of the Professional Master course, who have marked the structure of area 46 since the beginning to the present day. We can say that the Professional Master represents the real sense of the game for the area as part of the academic-scientific field. It also highlights the struggle and organization of the agents linked to Science and Mathematics Teaching for the non-fragmentation and maintenance of this space as an autonomous area in the field, even though this struggle has been lost partly. Nowadays, area 46 still faces several disputes for better positions in the field, such as the search for more fostering, recognition, autonomy, and participation in CAPES actions involving issues related to education.
A ÁREA 46 NA CAPES: ORIGEM, MUDANÇAS E CONSOLIDAÇÃO COMO “ENSINO” NO CAMPO ACADÊMICO-CIENTÍFICO
Keywords: Bourdieu's Field Theory; research area; Teaching Area